People of the screen: how evangelicals created the digital Bible and how it shapes their reading of scripture - Dyer, John (Oxford scholarship online, 2023)
'People of the Screen' traces the history of Bible software app development, showing the unique and powerful role evangelical entrepreneurs and coders have played in shaping its functionality and how their choices in turn shape the reading habits of millions of people around the world.